RE-NUM-OR: Python-based renumbering and reordering software for pedigree files - Kemal Yazgan (Czech Journal of Animal Science, 2018)
RE-NUM-OR is a new, flexible, and user-friendly renumbering and reordering data arrangement software for unprocessed pedigree files used in genetic evaluation systems for personal computers. RE-NUM-OR was written using Python (Ver. 2.7.13) 64 byte programming language and compiled with PyInstaller-3.2.1 software which is a set of utilities for freezing Python scripts into executable. RE-NUM-OR not only runs on 32 or 64 byte MS Windows but also runs on 64 byte GNU/Linux. The program has new, practical, and simple interface and the user does not need to create a parameter file for running the program and .txt, .xlsx or .et extension files can be used as input files directly. Output files (.txt, .xlsx, .et, .dat) can be obtained. For animal, sire and dam IDs, it can read all standard characters (ASCII codes from 32 to 126) in input files. The program supports both dot (.) and comma (,) for numerical data. Pedigree lines for parents do not need to be arranged prior to their progeny. If pedigree lines for parents follow their progeny, the program can detect this and it can reorder the animals as pedigree lines placing parents prior to their progeny. Another feature of this software is that it has a pop-up window with error notification. Also, it supports repeated observations. RE-NUM-OR executable, its user manual, and sample input files are available from www.kemalyazgan.com.tr.